Perspektif Anatomi Dan Antropometri Pada Senyum - Wita Anggraini (Jurnal Kedokteran Gigi Terpadu, 2020)
The main muscle that forms a smile is the m.zygomaticus major, which pulls the corners of the mouth to the superior and lateral. The m.zygomaticus major area is related to one's appearance, both when active or inactive. Smiles are fundamentally divided into “spontaneous” or “true” smiles ("Duchenne" smiles) and “fake” smiles or “social” smiles ("non-Duchenne" smiles). In "Duchenne" smile there is an additional contraction of the orbicularis oculi muscle so that the cheeks are raised and form wrinkles around the eyes. The contraction of orbicularis oculi muscle is very difficult to do voluntarily. Clinical smile analysis can be in the form of facial palpation by observing anatomical superficial landmarks of the face. Anthropometric measurements in smile analysis are recommended using standardized photographs with 8 main components of assessment: lip line, smile arch, upper lip curvature, buccal corridors, smile symmetry, occlusal frontal plane, dental components and gingival components. The purpose of this paper is to examine smiles in an anatomical and anthropometric perspective.